Efficacy of commercial neem-based insecticide, Nimbicidine® against eggs of the red flour beetle Tribolium castaneum (Herbst) - Das, Dipali Rani; Parween, Selina; Faruki, Saiful Islam (University Journal of Zoology, Rajshahi University, 2007)
The efficacy of different concentrations of the commercial neem-based insecticide, Nimbicidine® was evaluated against the eggs of the red flour beetle Tribolium castaneum (Herbst). The insecticide significantly inhibited the hatching, pupation and adult emergence of the beetle. The latent effects of Nimbicidine® on the next generation progenies were expressed by significant reductions in the growth of larvae, pupation and adult emergence coupled with lengthened developmental period, but the sex ratio was unaffected. Key words: Tribolium castaneum, Azadirachtin, hatching, pupation, adult emergence, growth and development, sex ratio Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.51-55